Implementasi Intrusion Detection System Dalam Upaya Pencegahan Cyber Attack - Ahmad Hidayat, Sendi; Darlis, Denny (eProceedings of Applied Science, 2024)
In this digital era, information systems havebecome the backbone for many organizations andcompanies. However, information systems are not free fromcyber attacks. Statistics from the National Cyber and Crypto AgencyState Cyber and Crypto Agency (BSSN) noted that there have been 370.02 million cyber attacksin Indonesia in 2022[1]. In order to avoidmaterial losses and immaterial losses caused by cyberattacks, organizations, companies, entitiesby cyberattacks, organizations, companies, government agencies and others are required to have a strongorganizations, companies, government agencies and others are required to have a system thatcan monitor, analyze vulnerabilities, and prevent cyber attacks.against cyber attacks. Wazuh is an openplatform that acts as an Intrusion Detection System (IDS)or as a threat detection system, security monitoringand incident response. Implementing Wazuh canbecome a defensive wall in an organizational body,company, government agency and so on inovercome cyber attacks. The implementation of vigilance has functionsfor Threat prevention, Integrity monitoring, Incidentresponse, Compliance in the server, Threat detection, LogEvent Management and Gap Detection that canminimize the occurrence of cyber attacks. Keywords - Cyber attack, Information system, Wazuh,Security monitoring, Threat detection